Student Activity Sheet Based on Inquiry for Supporting Practical Work in Solution Course - Ernita Vika Aulia; Wahono Widodo; Wahyu Budi Sabtiawan (Jurnal Pendidikan dan Pengajaran, 2022)
The Covid-19 pandemic has caused the government make policies by implementing online learning methods. Practical activities in the laboratory are not possible during online learning, so the lecturer develops student activity sheets as a practical guide at home with tools and materials that are easily found. This study aims to develop the validity and practicality of student activity sheets based on inquiry in the solution course, especially for making solutions from solid and liquid materials. Validity is viewed from the criteria of content, language, and presentation. Meanwhile, the practicality in terms of student activities during the learning process and student responses after the implementation of developed student activity sheets. The research method used is Research and Development (R&D) design and is limited only to a limited product trial stage. The research was conducted on 91 students majoring in science class. The research instrument consisted of validation sheets, student activity observation sheets, and student response questionnaires. Data analysis that used in this study is descriptive quantitatively with percentage techniques. The results indicate that the developed student activity sheets are valid and very valid category because it reaches a value of 2.9. The most dominant student activity is discussing with a group of friends. The student activity sheet also received good and very good (positive) responses from students because it reached a percentage of 61% with good and very good categories. So it can be concluded that the developed student activity sheets are declared feasible to be used in the learning process.